Modeling of the processes of functioning of an organizational and technical system based on Markov random processes - A. O. Zheleznyakov; R. A. Zhilin (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. In this paper, the main approaches to modeling the processes of functioning of the organizational and technical system, in particular the processes of maintenance and repair (MRO) of weapons, military and special equipment (VVST) by repair units of the operating organization (EO) using a mathematical model of Markov random processes, which will allow to evaluate the probabilistic characteristics of MRO processes of the VVST at carrying out activities of daily activities, which consist in carrying out work to restore the serviceability of the VST, as well as carrying out maintenance and operation of the OTS. Method. The modeling of processes is based on probabilistic models, in particular, the theory of random processes. Result. The use of a mathematical model of Markov random processes is justified. A graph of the states of the processes for maintenance and repair of VVST has been developed. A decision support system based on PTC Mathcad Prime has been implemented. The averaged generalized statistical information on the reliability of the VST was used as the initial modeling parameters in the work. Conclusion. The results obtained will make it possible to restore the serviceability and operability of the military-industrial complex both at the enterprises of the military-industrial complex and in the conditions of the operating organization without going beyond the time limits established in the regulatory and technical regulations. The considered approaches to modeling the processes of functioning of an organizational and technical system are a powerful tool for making informed and effective management decisions, they allow you to take into account many factors, conduct scenario analysis and optimize solutions, as well as use computers for more accurate and complex calculations.